(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the theme called linguo-cultural and linguistic study of the concept of ‘patience’, in which the linguo-cognitive direction is the importance of the concept of "mental lexicon" in cognitive linguistics generally, the concept and its significance, the concept of "Patience" is complex and different from the point of philosophical view, religious and linguo-philosophy and linguo-cultural studies. It is one of the various concepts. In addition, the article emphasizes that in modern society, it is important for every person and nation to approach closely related concepts such as "Patience" and "Tolerance" with a unique perspective. Although these two concepts are closely related to each other, at the same time they are different, the activation of the concept of "patience" in the Uzbek language, its idiomatic meaning and aspects reflected in phraseology are highlighted.